A CROSS SECTIONAL RESEARCH TO ANALYZE THE SHORTAGE OF NURSES IN SERVICES HOSPITAL LAHORE, PAKISTAN (The Research of Medical Science Review, 2025)
Background and Aim: The nursing shortage has been recognized as a global healthcare issue that can negatively impact the quality of patient care. Adequate staffing of nurses is an essential factor that can ensure the provision of high-quality healthcare services to patients. A shortage of nurses may lead to poor patient outcomes, including medication errors, patient falls, and hospital-acquired infections. Therefore, addressing the nursing shortage is critical to improve patient care and health outcomes.”The aim of this study was to investigate the shortage of nursing staff at Services Hospital, Lahore. Materials and Methods: A questionnaire-based survey was conducted at Services Hospital, Lahore. A total of 99 individuals from nursing staff participated in the study. Results: The study explores the demographics and workplace sentiments of nurses at Services Hospital, Lahore. Key findings include a predominantly female workforce (94.95%) and varying levels of job satisfaction. Concerns exist regarding job security and trust in organizational promises, while positive aspects include perceived influence on decisions and managerial support for family responsibilities. Recommendations include enhancing recruitment, retention initiatives, and transparent communication. Conclusion: The study sheds light on the demographics and sentiments of nurses at Services Hospital, Lahore, underscoring the need for targeted interventions to address concerns and capitalize on opportunities for workforce enhancement. Implementing recommendations for recruitment, retention, and communication can foster a more supportive and effective work environment.